PENINGKATAN HASIL BELAJAR MURID PADA PEMBELAJARAN IPAS MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA VISUAL INTERAKTIF DI KELAS IV SDN 05 TAROK DIPO KOTA BUKITTINGGI - Adinda Aurelia Azuhra; Mansurdin, Mansurdin; Hamimah, Hamimah; Zahara, Leni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This classroom action research aimed to improve students' learning outcomes in IPAS by implementing the Problem Based Learning model assisted by interactive visual media. The study involved 28 fourth-grade students of SDN 05 Tarok Dipo Bukittinggi and was conducted in two cycles. Data were collected through observation sheets, learning achievement tests, field notes, and documentation. The findings revealed improvements in lesson planning, classroom implementation, and students' learning outcomes. The average score increased from the pre-cycle stage to Cycle II. The use of interactive visual media encouraged students to participate actively, collaborate effectively, and understand historical content more easily. Therefore, Problem Based Learning assisted by interactive visual media can be used as an effective learning alternative in elementary schools.